2020
DOI: 10.1016/j.indcrop.2020.112320
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and 3D printability of poly (lactic acid)/acetylated tannin composites

Abstract: In this study, a three-dimensional (3D) printing filament prepared from poly (lactic acid) (PLA) and acetylated tannin via a twin-screw extruder was reported. The impact of acetylated tannin loading content on the final properties of the resulting composite materials and their 3D printability were investigated. The experimental results indicate that PLA can be compounded with up to 20 wt% acetylated tannin without any obvious deterioration in the tensile property. The resulting composites acquired better degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…In the final step, the residual weight of samples increases with increasing BT content due to the high char forming capacity of BT. This result is generally typical in polymeric composites containing phenolic compounds [10,36].…”
Section: Thermal Stabilitysupporting
confidence: 54%
“…In the final step, the residual weight of samples increases with increasing BT content due to the high char forming capacity of BT. This result is generally typical in polymeric composites containing phenolic compounds [10,36].…”
Section: Thermal Stabilitysupporting
confidence: 54%
“…Additionally, the PLA-1%T and PLA-2.5% nanocomposites decompose at 283 °C and 266 °C, respectively, with the highest decomposition rate at 387.4 °C and 382.2 °C, which are significantly lower than the previous ones. So, T filler has a strong catalytic effect and can markedly reduce PLA thermal stability because of the presence of highly polarized hydroxyl groups and low polarity PLA matrix, resulting in poor interfacial adhesion and dispersion of T in the PLA matrix [ 19 , 34 , 40 ]. Concerning the char residue of the nanocomposite materials, it was shown that for all the samples, the addition of both the two polyphenolic fillers tended to rise the char residue, as reported by previous studies [ 42 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhai et al [ 38 ] demonstrated that the onset of thermal degradation temperature and maximum thermal degradation temperature of PLA composites decrease with increasing filler content. Concerning the PLA-T composites, Anwer et al [ 39 ] and Liao et al [ 40 ] have shown that the onset of thermal degradation of PLA-T composites occurs at a slightly lower temperatures than neat PLA.…”
Section: Introductionmentioning
confidence: 99%
“…Such responsive materials utilizing tannin-based hybrid like materials have been developed in the recent past. For example, Liao et al [ 177 ] reported the successful EAM processing of a blend of PLA and acetylated condensed tannin (AT) and studied the effect of AT loading on polymer crystallinity, tensile properties, water absorption as well as degradation rate. PLA/AT blends with higher AT loading levels showed significantly higher water absorption and a decrease in crystallinity, which is favorable for faster degradation during exposure to the aqueous (especially alkaline) environment.…”
Section: Emerging Technological Opportunitiesmentioning
confidence: 99%